The Behaviorism Perspectives on English Learning: Its Theorical and Implications for Foreign English Learner in Online Learning Era - Bunga Nuur Primayu Utami (International Islamic Schools Alliance, 2021)
The successful of teaching learning process not only focus on the technique and the materials. Especially to learn English Subject the lecturer should attend in linguistic perspective especially in this case discuss about behaviorism perspective. Behaviorism is one of the learning perspectives centered on instructors for a long time, as an education regulator, shaping every aspect of the curriculum and commands. This paper presents an explanation of the characteristics of behavior, its philosophical and basic theory and the application of behaviorist theory to teach foreign language learner in Campus 7 Poltekkes Kemenkes Semarang in Environmental Health Department in online era. which has connection with theory which under pines the widely used Audio lingual Method by lecturers. In line, behaviorism perspective also has a close relationship with the audio lingual method to give reinforcement and encouragement to the students. So the important application in this case is the psychological aspects of students in the online era learning and is supported by the appropriate learning method.